Neutralization Heterogeneity of UK and South African Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Variants in BNT162b2-Vaccinated or Convalescent Coronavirus Disease 2019 (COVID-19) Healthcare Workers. (29th May 2021) - Marot, Stéphane; Malet, Isabelle; Leducq, Valentin; Abdi, Basma; Teyssou, Elisa; Soulie, Cathia; Wirden, Marc; Rodriguez, Christophe; Fourati, Slim; Pawlotsky, Jean-Michel; Boutolleau, David; Burrel, Sonia; et al.
Abstract: There are concerns about neutralizing antibodies' (NAbs') potency against severe acute respiratory syndrome coronavirus 2 variants. Despite decreased NAb titers elicited by BNT162b2 vaccine against VOC202012/01 and 501Y.V2 strains, 28/29 healthcare workers (HCWs) had an NAb titer ≥1:10. In contrast, 6 months after coronavirus disease 2019 mild forms, only 9/15 (60%) of HCWs displayed detectable NAbs against 501Y.V2 strain.